Semiotics curricula and modernization of rhetorical discourse - Muhammad Jabara, Muhammad Jassem (Journal of Tikrit University for Humanities, 2023)
The traditional rhetoric is no longer able to fulfill the aspirations of the contemporary reader in understanding and analyzing texts, so it has become a methodological necessity for Arabic rhetoric to keep pace with the approaches of modernity. The researchers sought to employ modern approaches in the development of Arabic rhetoric, drawing on contemporary Western treatises. We decided to investigate this issue, which is concerned with the development of the Arabic rhetorical lesson, and we found that semiotics curricula are the closest to rhetoric at the level of theory and application. Because of the limited scope in this research, we focused on theoretical issues to serve as a basis for what will come of application in other research projects. We have divided the research into an introduction and five axes: poetics and rhetoric, which focuses on differentiating between Arabic rhetoric and Western rhetoric; rhetoric and stylistics, and it discusses the opinions of researchers who made stylistics the legitimate heir of classical rhetoric; Semiology and Arabic rhetoric, which shows the forms of compatibility between the two approaches, and the principles of semiology between theorizing and application. It focuses on differentiating between the science of signs and the science of semantics, and it paves the way for transforming theoretical issues and turning them into practical issues through the concept of image. And the semiology of publicity, which is the last axis that seeks to address contemporary issues related to advertising methods and the exploitation of rhetorical imagery between the mental image and the visual image. Through these axes, we presented a group of previous Arab studies that presented important theses in this field, as well as Western theses to be more like a comparison between the Arab and Western tracks.